Perceived parental alcohol problems and later dropout and grade point average in high school: A register‐based follow‐up study. (7th February 2023) - Pisinger, Veronica Sofie Clara; Møller, Sanne Pagh; Andersen, Susan; Tolstrup, Janne S.
Abstract: Introduction: The aim of the study was to test the hypothesis that young people with perceived parental alcohol problems have higher dropout rates in high school and lower grade point average (GPA) at graduation compared to young people without perceived parental alcohol problems. Methods: Data come from Danish National Youth Study 2014 ( n = 62, 171), merged with register‐data on later dropout of high school and GPA. Multilevel Poisson regression models of incidence rates of dropout and multilevel linear models of GPA were used to assess the association with perceived parental alcohol problems. Results: A total of 6.6% of the students perceived their parent(s) to have alcohol problems. Young people with perceived parental alcohol problems had higher dropout rate (girls incidence rate ratio 1.83; 95% confidence interval [1.62–2.06]); boys (incidence rate ratio 1.38; 95% confidence interval [1.17–1.64]) and lower grades (GPA: −0.24; 95% confidence interval [−0.32; −0.17]) compared to those without. There was no statistically significant difference between mother's and fathers' alcohol problems in the associations with dropout and GPA. Discussion and Conclusions: Perceived parental alcohol problems were associated with higher incidence rate ratio of dropout and lower grades within all categories of the socioeconomic factors. Our results show that young people with perceived parental alcohol problems have higher high school dropout rates and lower grades compared to those without perceived parental alcohol problems across gender and socioeconomic position. The results call for evidence‐based interventions to support young people with parental alcohol problems in the educational system.